State Secularization and Religious Resurgence: Diverging Fates of Secularism in Turkey and Iran - Başkan, Birol (Politics and religion, 2014)
The recent Arab revolutions/rebellions/protests have raised once again an old question: what features should the Arab political systems ideally have? Inescapably, perhaps, the case of Turkey frequently appears as a model to be emulated in the Arab world. A variety of actors, from George W. Bush to Barack Obama, from Rashid Ganouchi to Hillary Clinton has in fact viewed Turkey in that role. Even though, many intellectuals and academics usually raise doubts about the suitability of Turkish model for the Arab world (see, for example, Mamedov and Makarov 2011), it may still prove fruitful to consider the case of Turkey more seriously.